Learning Dynamics across Boundaries of IS Context: A Structural perspective to Support Knowledge Management - Castro Gonçalves, Luciana (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2012)
This paper seeks to analyze the extent to which organizations can learn in an Information System (IS) context by focusing on the relationship between projects and communities of practice. Adopting a theoretical framework combining the social learning literature (Lave, 1991; Wenger; 1998, Orlikowski, 2002) and a structural approach (Giddens, 1984), we used an ethnographic study to examine two contrasting learning dynamics in the IS Department of a multinational car manufacturer. Our findings highlight embeddedness and facilitating and inhibiting factors in learning process. Our discussion suggests an integrated knowledge management perspective (Pawlowski, Robey, 2004; Levine, Xin, 2007, Srikantaiahet al., 2010).